1971
DOI: 10.1128/aem.22.6.1152-1158.1971
|View full text |Cite
|
Sign up to set email alerts
|

Observations by Electron Microscopy on Pig Muscle Inoculated and Incubated with Pseudomonas fragi1

Abstract: Myofibrils from pig muscle inoculated and incubated with Pseudomonas fragi showed an extremely disrupted appearance as compared to uninoculated controls. There was an almost complete absence of material in the H zone, marked disruption of the A band (probably myosin), and some loss of dense material from the Z line. These changes indicated that marked proteolysis had occurred. Bacteria observed in spoiled muscle tissue exhibited protrusions or blebs on the outer surface of the cell walls. The blebs appeared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
24
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 10 publications
5
24
0
Order By: Relevance
“…Pseudomonas fragi secreted aldolase, glyceraldehyde phosphate dehydrogenase, lactic dehydrogenase, and creatine kinase in the sarcoplasm of rabbit and porcine muscles, which led to muscle breakdown (Hasegawa et al, 1970). Early electron microscopic images of P. fragi growth on porcine muscle have depicted extensive degradation of myofibrils compared to the uninoculated controls (Dutson, Pearson, Price, Spink, & Tarrant, 1971). Authors also reported marked proteolysis where there was a severe loss of material in the H zone and marked disruption of the A band, as well as loss of dense material from the Z line of the porcine skeletal muscle tissue (Dutson et al, 1971;Hasegawa et al, 1970).…”
Section: Enzymatic Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…Pseudomonas fragi secreted aldolase, glyceraldehyde phosphate dehydrogenase, lactic dehydrogenase, and creatine kinase in the sarcoplasm of rabbit and porcine muscles, which led to muscle breakdown (Hasegawa et al, 1970). Early electron microscopic images of P. fragi growth on porcine muscle have depicted extensive degradation of myofibrils compared to the uninoculated controls (Dutson, Pearson, Price, Spink, & Tarrant, 1971). Authors also reported marked proteolysis where there was a severe loss of material in the H zone and marked disruption of the A band, as well as loss of dense material from the Z line of the porcine skeletal muscle tissue (Dutson et al, 1971;Hasegawa et al, 1970).…”
Section: Enzymatic Activitymentioning
confidence: 99%
“…Early electron microscopic images of P. fragi growth on porcine muscle have depicted extensive degradation of myofibrils compared to the uninoculated controls (Dutson, Pearson, Price, Spink, & Tarrant, 1971). Authors also reported marked proteolysis where there was a severe loss of material in the H zone and marked disruption of the A band, as well as loss of dense material from the Z line of the porcine skeletal muscle tissue (Dutson et al, 1971;Hasegawa et al, 1970). Enzymatic activity of P. fragi has a deleterious effect on the color of meat stored at chilled temperatures.…”
Section: Enzymatic Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…They were able to demonstrate changes in both the sarcoplasmic and myofibrillar proteins of minced pork meat inoculated with pure cultures of several different bacteria and incubated at refrigeration temperatures. Pseudomonas fragi produced the greatest changes and its activity in minced pork muscle was studied further by (a) comparing the appearance of its extracellular proteinase with the onset of spoilage odours and protein breakdown (Tarrant, Pearson, Price & Lechowich, 1971); (b) examining myofibrillar structure during storage by electron microscopy (Dutson et al, 1971) and (c) following the effect of partially purified proteinase on ground muscle and on isolated myofibrillar and sarcoplasmic proteins (Tarrant, Jenkins, Pearson & Dutson, 1973). In most of these experiments, slime and spoilage odours were apparent at the earliest sampling times used and no data relating to the prespoilage period of storage were reported.…”
mentioning
confidence: 99%